A framework for the Efficiency Evaluation of Ireland's Electricity Power System using Data Envelopment Analysis (DEA) - Mullarkey, Shane (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2013)
The complex modem Electricity Power System (EPS) is the most significant pervasive infrastructure underpinning the social, technological, and economic development of modem economies The context in which modern EPSs operate is consistently evolving. EPSs face dynamic challenges in the form of market liberalisation, increased competition and interconnection, sustainability, mitigating CO2 emissions, fuel price volatility, issues of security of supply, the introduction of new and varying sources and most importantly improving energy efficiency. The European Union (EU) has set a number of 2020 energy efficiency targets which include i) 20% reduction in Greenhouse Gas (GHG) emissions ii) increasing the share of renewable energy in final energy consumption to 20%, and iii) reducing total consumption relative to projections by 20%. These challenges will require a shift from the present centralised, base loaded, fossil fuel paradigm towards a dispersed, multi generation technological, renewables supported energy efficient EPSs of significantly greater complexity.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin